2017
DOI: 10.1016/j.cose.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

DRAW-A-PIN: Authentication using finger-drawn PIN on touch devices

Abstract: This paper presents DRAW-A-PIN, a user authentication system on a device with a touch interface that supports the use of PINs. In the proposed system, the user is asked to draw her PIN on the touch screen instead of typing it on a keypad. Consequently, DRAW-A-PIN could offer better security by utilizing drawing traits or behavioural biometrics as an additional authentication factor beyond just the secrecy of the PIN. In addition, DRAW-A-PIN inherently provides acceptability and usability by leveraging user fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 39 publications
(64 reference statements)
0
27
0
1
Order By: Relevance
“…Shahzad et al [16] proposed an authentication scheme based on users' particular behavior when they perform a touch gesture and a signature. Nguyen et al [13] proposed an authentication scheme called DRAW-A-PIN, which required users to draw a PIN on touchscreen instead of typing. Their system particularly employed a Content Analyzer and a Drawing Behaviour Analyzer to identify imposters.…”
Section: Related Workmentioning
confidence: 99%
“…Shahzad et al [16] proposed an authentication scheme based on users' particular behavior when they perform a touch gesture and a signature. Nguyen et al [13] proposed an authentication scheme called DRAW-A-PIN, which required users to draw a PIN on touchscreen instead of typing. Their system particularly employed a Content Analyzer and a Drawing Behaviour Analyzer to identify imposters.…”
Section: Related Workmentioning
confidence: 99%
“…Then, in Block6, users had to repeat once the same task considered in Block5 but this time in an invisible mode, i.e., we did not provide to the users any visualization of the numbers while drawing them. The main motivation of this novel acquisition scenario is to protect us against shoulder surfing attacks, as commented in [22]. In Block 7, users had to draw each number of the password inside each of the four available boxes (two times), considering first a visible mode (see Fig.…”
Section: B Mobiletouchdbmentioning
confidence: 99%
“…Signing with a finger over a display also allows the taking into account of tapping behavior [276]. In fact, it has been shown that touch analysis can be used to recognize users [87,179].…”
Section: Signing On Touchscreensmentioning
confidence: 99%